Curriculum Integration and Epistemological Identity in Indonesian Madrasahs: A Post-Reform Analysis - Faza, Irfany Awaludin; Hanafi, Subhanal; Husnaini, M. (Program Studi Aqidah dan Filsafat Islam, 2025)
Curriculum integration in Indonesian madrasahs has been promoted as a strategic policy to align Islamic education with the national education system in the post-Reform era. While this integration aims to strengthen institutional legitimacy and improve competitiveness, it also raises critical questions regarding the epistemological orientation and identity of madrasahs. This study examines curriculum integration in Indonesian madrasahs as an epistemological issue rather than merely a technical or administrative arrangement. Employing a qualitative library research design with a philosophical–analytical approach, this study analyzes national education policy documents—particularly Law Number 20 of 2003 and the Decree of the Minister of Religious Affairs (KMA) Number 183 of 2019—alongside relevant scholarly literature on Islamic education reform. The findings indicate that the frequently cited 70:30 proportion between general and religious subjects does not represent an explicit regulatory mandate, but rather functions as an analytical abstraction derived from the structural organization of the madrasah curriculum. Interpreted through Syed Muhammad Naquib al-Attas’s framework of the de-secularization (Islamization) of knowledge, the study reveals an epistemological tension in which general sciences tend to assume a dominant structural position, potentially positioning religious knowledge as supplementary. This condition reflects an identity dilemma shaped by the interaction between Islamic worldview–based education and policy-driven standardization. The study concludes that sustainable curriculum integration in madrasahs requires an epistemological foundation rooted in tawhid and adab to support holistic human development and prevent epistemological fragmentation.